2014
DOI: 10.1155/2014/237821
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Corticosteroid Treatment in Stevens-Johnson Syndrome and/or Toxic Epidermal Necrolysis over a Period of 10 Years in Vajira Hospital, Navamindradhiraj University, Bangkok

Abstract: Background. Stevens-Johnson syndrome (SJS) and/or toxic epidermal necrolysis (TEN) are uncommon and life-threatening drug reaction associated with a high morbidity and mortality. Objective. We studied SJS and/or TEN by conducting a retrospective analysis of 87 patients treated during a 10-year period. Methods. We conducted a retrospective review of the records of all patients with a diagnosis of SJS and/or TEN based on clinical features and histological confirmation of SJS and/or TEN was not available at the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 14 publications
2
22
2
3
Order By: Relevance
“…Patients with TEN have a more severe disease and are likely to have longer hospital stay than patients with SJS. However, these findings were less significant than those reported in a previous study in Thailand 28. In particular, a longer hospital stay was observed among SJS–TEN patients than among TEN patients in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Patients with TEN have a more severe disease and are likely to have longer hospital stay than patients with SJS. However, these findings were less significant than those reported in a previous study in Thailand 28. In particular, a longer hospital stay was observed among SJS–TEN patients than among TEN patients in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Toxic epidermal necrolysis (TEN) and Stevens–Johnson syndrome (SJS) are severe, life‐threatening, mucocutaneous reactions with high mortality and are currently considered to represent different levels of severity of the same disease. Although most cases of TEN/SJS are thought to be caused by drug reactions, they may also be related to Mycoplasma pneumoniae infection and herpes simplex virus . Both TEN and SJS may cause damage to multiple organ systems and may cause skin pain (erythema, blisters, extensive epidermal exfoliation), eye, mouth and genital mucosa reactions, and multiple organ dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Although specific treatment has not been indicated, current systemic treatment includes corticosteroids, intravenous immunoglobulin (IVIG), and cyclosporine. Previous studies have shown that these treatments can reduce mortality and improve patient prognosis . However, the systemic application of corticosteroids and their usage and dosage are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Kardaun et al (17) reported that use of high dose corticosteroid for short-term was helpful. In the retrospective study of Roongpisuthipong et al (18) published in 2014, it was reported that use of short-term corticosteroid contributed to reduction in mortality rates. However, there are also studies which reported that steroid treatment did not contribute additionally to care therapy (16).…”
Section: Discussionmentioning
confidence: 99%